Tisztesség és bizalom: Kornai J. and Rose-Ackerman, S. eds.: Tisztesség és bizalom a posztszocialista átmenet fényében I-II. Budapest: Nemzeti Tankönyvkiadó, 2005. [Building a Trustworthy State: Problems of Post-Socialist Transition. Volume I.; Creating Social Trust: Problems of Post-Socialist Transition. Volume II.] (Szociológiai Szemle, 2024)
-